Odpowiedzi

2010-01-21T17:05:46+01:00
Oblicz wartość liczbową wyrażenia:
a) 4x-(x+6)+4 = dla x=1/3
=4x-x-6+4 =
= 3x-2 =
= 3*1/3-2 = 1-2 = -1

b) (x+1)-(x-2)+10 = dla x=2,2
= x+1-x+2+10 =
= 13

c) (a+4b)-(5+2a)-(3b-5)= dla a= -0,1 i b= 0,2
= a+4b-5-2a-3b+5 =
= -a+b =
= 0,1+0,2 = 0,3

d) (-a+2ab-1)-(a-4ab+5) = dla a=1/4 i b=2
= -a+2ab-1-a+4ab-5 =
= -2a+6ab-6 =
= -2*1/4 + 6*1/4*2-6 =
= -1/2+3-6 =
= -0,5+3-6 =
= 2,5-6 = -3,5
154 4 154
dzięki
Komentarz został usunięty
Źle w d)
w b) jest x do potęgi 2